2015
DOI: 10.1210/en.2015-1345
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Calcitonin Receptor to Limit Bone Loss During Lactation in Female Mice by Inhibiting Osteocytic Osteolysis

Abstract: During lactation, the large transfer of calcium from the mother to the milk is primarily sourced from the maternal skeleton. To determine whether the calcitonin receptor (CTR) plays a physiological role to protect the skeleton from excessive resorption during lactation, we assessed the maternal skeleton of global CTR knockout (CTRKO) and littermate control mice at the end of lactation (postnatal day 21). Micro-computed tomography analyses showed no effect on trabecular or cortical bone in the distal femur and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 39 publications
3
36
0
1
Order By: Relevance
“…During lactation these conditionally deleted Ctr null mice show a greater increase in osteocyte lacunar size compared with WT, suggesting that loss of calcitonin signaling leads to increased osteocytic osteolysis (187). However, there were no significant differences in bone structure by microCT or histomorphometry between Ctr nulls and WT (187). Moreover, prolactin was significantly reduced, which is the opposite of what was expected given that targeted overexpression of calcitonin in the pituitary, and pharmacological treatment with calcitonin, both reduce prolactin.…”
Section: Animal Datamentioning
confidence: 82%
See 1 more Smart Citation
“…During lactation these conditionally deleted Ctr null mice show a greater increase in osteocyte lacunar size compared with WT, suggesting that loss of calcitonin signaling leads to increased osteocytic osteolysis (187). However, there were no significant differences in bone structure by microCT or histomorphometry between Ctr nulls and WT (187). Moreover, prolactin was significantly reduced, which is the opposite of what was expected given that targeted overexpression of calcitonin in the pituitary, and pharmacological treatment with calcitonin, both reduce prolactin.…”
Section: Animal Datamentioning
confidence: 82%
“…This results in Ͼ90% but not 100% loss of CTR expression in kidneys and osteoclasts; expression in other tissues relevant to lactation, especially mammary tissue and pituitary, were not assessed. During lactation these conditionally deleted Ctr null mice show a greater increase in osteocyte lacunar size compared with WT, suggesting that loss of calcitonin signaling leads to increased osteocytic osteolysis (187). However, there were no significant differences in bone structure by microCT or histomorphometry between Ctr nulls and WT (187).…”
Section: Animal Datamentioning
confidence: 87%
“…This study shows that healthy osteocytes can both remove and replace their perilacunar matrix thereby playing a role in mineral homeostasis during calcium demanding conditions. Recently it has been shown that the Calcitonin Receptor may also play a role by inhibiting perilacunar remodeling with lactation 41 .…”
Section: Normal Osteocyte Functionsmentioning
confidence: 99%
“…The expression of genes known to be utilized by osteoclasts to remove bone, including tartrate-resistant acid phosphatase (TRAP) and cathepsin K, carbonic anhydrase 2 and matrix metalloproteinases is elevated in osteocytes from lactating mice (5557). Furthermore, recent work demonstrated that global deletion of the calcitonin receptor leads to increased osteocytic, but not osteoclastic, osteolysis during lactation, providing the first evidence for a physiological role of the calcitonin receptor to protect the maternal skeleton from bone loss during lactation by direct actions on osteocytes (58). Although the physiologic implications of these observations remain to be determined, this data suggests that, as previously described for phosphate metabolism, osteocytes also contribute to calcium mobilization and mineral homeostasis through perilacunar remodeling as has been proposed earlier(1;59).…”
Section: Regulation Of Bone Resorption By Osteocytesmentioning
confidence: 99%